Inhibition of alkaline flocculation by algal organic matter for Chlorella vulgaris. (1st January 2016) - Vandamme, Dries; Beuckels, Annelies; Vadelius, Eric; Depraetere, Orily; Noppe, Wim; Dutta, Abhishek; Foubert, Imogen; Laurens, Lieve; Muylaert, Koenraad
Abstract: Alkaline flocculation is a promising strategy for the concentration of microalgae for bulk biomass production. However, previous studies have shown that biological changes during the cultivation negatively affect flocculation efficiency. The influence of changes in cell properties and in the quality and composition of algal organic matter (AOM) were studied using Chlorella vulgaris as a model species. In batch cultivation, flocculation was increasingly inhibited over time and mainly influenced by changes in medium composition, rather than biological changes at the cell surface. Total carbohydrate content of the organic matter fraction sized bigger than 3 kDa increased over time and this fraction was shown to be mainly responsible for the inhibition of alkaline flocculation. The monosaccharide identification of this fraction mainly showed the presence of neutral and anionic monosaccharides. The addition of 30–50 mg L −1 alginic acid, as a model for anionic carbohydrate polymers containing uronic acids, resulted in a complete inhibition of flocculation. These results suggest that inhibition of alkaline flocculation was caused by interaction of anionic polysaccharides leading to an increased flocculant demand over time. Graphical abstract: Highlights: Inhibition of alkaline flocculation is increased over time for Chlorella vulgaris . Inhibition is mainly caused by changes in medium composition. The addition of alginate caused total inhibition of flocculation. Anionic polysaccharides or glycoproteins > 3 kDa are believed to cause inhibition.